Responses of Solo Garlic Crops Grown at Low Elevation of Tropical Areas to Organic Matter and Paclobutrazol - Suharjo, Usman Kris Joko; Widodo; Pamekas, Tunjung; Monica (Akta Agrosia, 2024)
Solo garlic has been known for its medicinal benefits because of which it is considerably expensive. Nonetheless, no Indonesian farmer produces solo garlic intentionally since no information on how to grow solo garlic in Indonesia is available.  Growers, usually harvest 5-10 kg of solo garlic from 1 hectare of garlic crop they grow. A greenhouse experiment was conducted from November 2018 to January 2019 at the Department of Agronomy, Faculty of Agriculture, Bengkulu University, about 10 m above sea level to study the effects of paclobutrazol and organic matter on the เว็บสล็อต | R4shub growth and yield of solo garlic crop grown at low elevation of Bengkulu. The experiment used completely randomized design arranged in factorial (2 factors; 5 replications). The first factor tested was organic matter levels (0, 2.5, 5.0, 7.5%) and the second factor was paclobutrazol concentrations (0, 500, 1000, 1500 ppm). Solo garlic seeds were planted in the polybag filled with 5 kg of media, a mixed of topsoil and organic matter. The crops were sprayed with paclobutrazol at 21, 35, and 49 days after planting.  The results showed that organic matter did not significantly affect crop growth and yield. In contrast, paclobutrazol significantly affected crop growth and yield, with the best yield was found at 1500 ppm paclobutrazol. Furthermore, there was no significant interaction between organic matter and paclobutrazol on the growth and yield of solo garlic grown at low elevation at tropical climate in Indonesia. Keywords: clove, medicine, organic matter, paclobutrazol, solo garlic